Técnica de videoceloscopia para sexagem em surubim (pseudoplatystoma coruscans x pseudoplatystoma reticulatum) - Glauco Vinício Chaves (2011)
The surubim (Pseudoplatystoma spp.) is a priority specie for the development of national aquaculture. The absence of sexual dimorphism makes it difficult to determine the gender, becoming reproductioninaccurate, and individuals need to keep for 2 to 3 years until you get sexing. The objective was to determine and certify the technique for sexing videoceloscopy early in surubim. We used 113 surubinshybrids (P. reticulatum x P. coruscans) divided into three groups on weight, ranging from 144 to 904g. All were anesthetized with quinaldine, coelomic cavity insufflated with CO2 and a 2.7 mm endoscope was inserted to 2cm cranial to the right pelvic fin to visualize the gonads. The time spent on sexing averaged 6.8 + 1.95 min. After 21 days all fish were euthanized and was compared via videoceloscopic sexing with the macroscopic and histology of the gonads and it was achieved 99,1%accuracy with 6.2% mortality